(untitled) (City: History, Culture, Society, 2022)
After being widely explored in the historiography of Western architecture, postmodernism has only recently started receiving adequate attention in Eastern and Central Europe. The phenomenon of postmodernism developed beyond the borders of the Soviet world, so the so-called “cultural logic of late capitalism” crossing the boundaries of the Iron Curtain has to be considered a consequence of globalization. On the other hand, this global trend was synchronized with the local expression of architecture: the pursuit of identity, attention to context and continuation of architectural traditions. Soviet publications presented postmodernism as a foreign phenomenon, but simultaneously noted that it could be useful to local architects as well. This did not imply an invitation to imitate Western colleagues, but rather signalled that certain architectural values had become globally significant to both, the capitalist and socialist industrial world. The text aims to uncover the local translations of (post)modernity in Lithuania in the context of the tendency’s peak period: the final decades of Soviet rule.